(untitled) (Journal of Engineering, 2008)
The Digital Elevation Model (DEM) considered a common tool in producing topographic maps, orthophotos and civil engineering projects besides other different engineering applications. As a result many software packages were developed and used to produce DEM from different sources like field surveys, scanned topographic maps and stereo photos exposed from air or space. This paper is devoted to evaluate the most suitable and accurate interpolation method in producing digital elevation model for the data gathered from existed topographic maps which are also compared with data gathered from field survey. Map scale (1:25000) with contour interval (50m) were chosen in the tests. The accuracy tests based on the National Mapping Accuracy Standards (NMAS) by comparing the result of Root Mean Square Error (RMSE) in elevations with the typical standard deviation (σz) proposed by (NMAS) which depends on the scale of maps and contour intervals. From testing four interpolation techniques ((Kriging, Triangulated Irregular Network (TIN), Inverse Distance Weighting (IDW) and Polynomial)) it was found that kriging is the best method followed by TIN method while IDW method failed in some tests, and the polynomial model failed in all tests